Landasan Sosiologis dan Pedagogis Manajemen Pendidikan Islam - Yuli Umro’atin; Asrop Syafi’i (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2023)
The presence of Islamic education management is the right solution to realizing real education, as describedin the Qur’an and Hadith, apart from being a philosophy it can also be realized in real educational historicalpractice to create independent and creative individuals. This research goals to explain the Sociological andPedagogical foundations in Islamic education management, a long with urgency of the Sociological andPedagogical foundations in Islamic Education Management. This study uses a literature study in whichall results and discussions are sourced from books and journal articles. The results and discussion include:One of the principles in the foundation of Islamic Education Management is the principle of society, namelythe understanding that humans are social beings, not individuals. Management of Islamic Education frompedagogical perspective in Islam is prepared to create a generation that is capable, independent.